Reuniting families : supporting mothers regaining custody following substance use : a thesis presented in partial fulfilment of the requirements for the degree of Master of Social Work at Massey University, Manawatū, New Zealand - Hadfield, Susan Winifred (Massey University, 2026)
Parents’ substance use is a risk in child welfare cases, exacerbated by poor mental health, adverse childhood experiences, and violence which is further compounded by having multiple children at a young age (Buek & Mandell, 2023). Mothers are required to cooperate with child welfare, when their history supports distrust, and they lack social supports, education, employment, and stable housing. This qualitative research explored ways to support mothers to regain custody of their children following a history of substance use in Aotearoa New Zealand. It considered the difficulties mothers face in family reunification, the services needed to empower mothers towards reunification, as well as post-reunification, to ensure ongoing stability of care. Drawing on social constructionism as a theoretical framework, eight semi-structured interviews were conducted with three groups of participants: mothers, social workers and carers. Key findings include that: mothers face challenges related to addressing historical issues, accessing support, and addressing caregiver concerns; social workers fulfil important roles in working with mothers and prioritise relationship-based practice, support interagency collaboration, and facilitate turning points for mothers. Additionally, the research found that caution is advised when placing children in paternal kinship care when the father perpetrated violence as this can put mothers at risk of further abuse, and that formal support needs to continue for mothers and children post-reunification. This research recommends social workers employ relationship-based practice, consider the ongoing safety of mother and child when placing children in care, and that tailored support for mothers and children be available pre-removal, during separation, and post-reunification.
Keywords: 440901 Clinical social work practice